(RE)MEANING IMAGES: READING AND REINTERPRETATION PRACTICES IN ART TEACHING - Baliscei, Joao Paulo; Teruya, Teresa Kazuko [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2015)
In this work, we aim to analyze the concept and characteristics of image readings and reinterpretations, which are recurring exercices in art teaching. To do so, we highlight a few differences and connections between these two practices. We also report a project developed with the students of three classes of the 9th year of elementary school, in 2011, in Guarapuava, located in the state of Parana, where were made visual readings and reinterpretations. For the performance of the activities, we based in Pablo Picasso. s Guernica. The results presented demonstrated that in both the readings and the reinterpretations, the likings, interests and previous and personal knowledges of the students influenced their perception and visual interpretation. Furthermore, we divided the reinterpretations in three groups with distinct characteristics. Finally, we consider that both the readings and the reinterpretations of the images are constructed in the interaction between the students, the contest in which they live, their subjectivity and visual artifacts of their daily lifes.
Keywords: Art teaching; Visual studies; Guernica